(untitled) (TEST Ticontre. Theory Text Translation, 2023)
Focusing on Works (2016, 2022²), the article examines one of the most peculiar aspects of Vitaliano Trevisan’s narrative writing, i.e. the tendency towards a broad and hypotactic syntax, correlating it with some features of his narrative technique and with some recurring thematic areas. Starting from the metatextual notations and the author’s scattered observations of poetics, linguistic and narrative form is valued as a constitutive trait of the subject and its representation. Prendendo ad oggetto Works (2016, 2022²), l’articolo esamina uno degli aspetti più peculiari della scrittura narrativa di Vitaliano Trevisan, cioè la tendenza ad una sintassi ampia e ipotattica, mettendolo in correlazione con alcuni tratti della sua tecnica narrativa e con alcune aree tematiche ricorrenti. Muovendo dalle notazioni metatestuali e dalle sparse osservazioni di poetica dell’autore, forma linguistica e narrazione vengono valorizzate come dimensioni costitutive del soggetto e della sua rappresentazione.